The Effect of Picture Storybook Media on the Reading Ability of Class II Students - Sa’idatul Hasanah; Sahkholid Nasution (Dinasti International Journal of Education Management And Social Science, 2024)
This research aims to determine the effect of using picture storybook media on the reading ability of class II students at SDS Al-Washliyah 11 Medan Amplas District. This research uses a quantitative approach with pre-experimental methods, using a one-group pretest-posttest design. The research sample consisted of 32 students, with a total sampling technique. Research instruments include tests, observations and interviews. Data were analyzed using SPSS version 25, with normality, homogeneity and paired sample t-tests. The research results showed that there was a significant increase in students' reading ability after using picture storybook media, with an average pretest score of 51.09 and posttest of 80.00. The significance of the t test shows a value of  0.00 < 0.05, which means there is a significant difference between the pretest and posttest results. Thus, the use of picture storybook media has a positive effect on students' reading abilities.